Multiple regression modeling of natural rubber seismic-isolation systems with supplemental viscous damping for near-field ground motion - Alhamaydeh, Mohammad H.; Barakat, Samer A.; Abed, Farid H. (Journal of Civil Engineering and Management, 2013)
This work presents the development and implementation of the Multiple Regression Analysis (MRA) model to Seismic-Isolation (SI) systems consisting of Natural Rubber Bearings and Viscous Fluid Dampers subject to Near-Field (NF) earthquake ground motion. A model representing a realistic five-story base-isolated building is used. Several damper properties are used in creating an array of feasible combinations for the SI system. Two ensembles of seven NF earthquake records are utilized representing two seismic hazard levels. The key response parameters investigated are the Total Maximum Displacement, the Peak Damper Force and the Top Story Acceleration Ratio of the isolated structure compared to the fixed-base structure. Mathematical models for the key response parameters are established via MRA. The MRA models produced acceptable results with significantly less computation. This is demonstrated via a practical example of how the MRA models would be incorporated in the design process, especially at the preliminary stages.